(untitled) (Research, Society and Development, 2020)
Objective: To report the case of a patient after cancer treatment and evaluate the impact of oral health on quality of life, through the Oral Health Impact Profile (OHIP-14) before, during, and after dental treatment. Methodology: A patient after antineoplastic treatment attended the clinic specialized. In all consultations, OHIP-14 was applied. Case report: A 68-year-old man diagnosed with keratinizing squamous cell carcinoma of the larynx (T3N0MX), undergoing chemotherapy and adjuvant radiotherapy (2878.2 Grays) and vertical partial laryngectomy surgery without ganglionic emptying. After CT, he complained of tooth loss and discomfort in the tongue after radiotherapy. Ex-drinker for 5 years, ex-smoker for 6 months, but alcoholic for> 10 years and smoker <50 years. Side effects of antineoplastic treatment included labial dryness, hyposalivation, dental fractures, residual roots, changes in swallowing, pain during mouth opening, and cervical movement. The results OHIP-14 was medium (17.85), weak (3.52), weak (2.84) and null impact of oral health on quality of life in the initial consultation, throughout the dental treatment, at the end of dental treatment and 1 year and 2 months after dental treatment, respectively. There was a high impact on psychological discomfort (3.55), medium on psychological disability (1.6), and functional limitation (2.04), in 2015, 2017, and 2018, respectively. Conclusion: The performance of the dentist on the late oral effects of chemotherapy and radiotherapy had a positive impact on improving the quality of life after cancer treatment, with the help of the multidisciplinary team.